Spatiotemporal dynamics of water spread areas and vegetation health in the lower Vaigai sub-basin: A multi-sensor analysis using Sentinel-1A SAR and Sentinel-2A MSI (2018-2023) - Harshavardhan, P M; Sivamurugan, A P; Pazhanivelan, S; Ragunath, K P; Suganthi, A (Plant Science Today, 2024)
A spatiotemporal analysis of water spread areas in tanks within the lower Vaigai sub-basin was performed using Sentinel-1A SAR imagery from 2018 to 2023. The analysis revealed a mean water spread area of 275.29 ha, with the highest being 628.29 ha in summer 2023 and the lowest at 5.55 ha in summer 2018. This was influenced by a total rainfall of 5777.06 mm, with an average of 879.14 mm annually. NDVI data from Sentinel-2 categorized crop health across 74.5 thousand ha, showing high no vegetation (20-45 %) and sparse vegetation (24-33 %) during the Kharif season. The Rabi season exhibited improved conditions, with moderate vegetation peaking at 40 % in 2020, while summer consistently showed crop stress with minimal good vegetation (up to 5 %). Given the arid conditions and dependence on irrigation tanks, the study underscores the importance of water availability for crop growth in lower Vaigai sub basin. In this investigation, the identification of poor crop performance during the Kharif and summer seasons can guide researchers and administrators to increase efforts on introduce drought-resistant crops, adjust planting schedules or implement supplemental irrigation over this region. Additionally, the insights gained from the present investigation on water spread dynamics in tanks recommend the development of climate-smart agricultural practices, including water-saving irrigation techniques and hydrological modelling, to enhance resilience. The results can further support government interventions, such as improving tank rehabilitation programs, which are crucial for ensuring sustainable crop production and food security in the Lower Vaigai sub-basin.